Pengaruh Pelatihan Kerja Dan Motivasi Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening : Study Kasus Pada Bagian Transportasi Karyawan Kontrak Supir Bus Inalum PT. Auto Padu Kuala Tanjung Batu Bara - Sagala, Yomeini; Ramadhani, Miranti; Khairunnisa, Khairunnisa (Management And Business Progress, 2023)
This study aims to determine the effect of job training and motivation on employee performance with work discipline as an intervening variable (Case study in the transportation section of contract employees, Inalum bus drivers PT. Auto Padu Kuala Tanjung Batu Bara). The sample in this study amounted to 32 people, namely all contract employees of Inalum bus drivers PT. Auto Blend. This sampling uses a total sample, where the entire population is sampled. Data collection techniques using interviews, questionnaires and observation. The data analysis technique used is instrument test, classic assumption test, multiple linear regression test, coefficient of determination and hypothesis testing. The results of equation I multiple linear Z = 7.730 + 0.259X1 + 0.243X2 and equation II multiple linear Y = 5.732 + 0.424X1 + 0.766X2 - 0.454Z. Based on hypothesis testing using the t test (partial) that job training (X1) has no significant effect on work discipline (Z), motivation (X2) has no significant effect on work discipline (Z), job training (X1) has no significant effect on employee performance (Y), motivation (X2) has a significant positive effect on employee performance (Y), work discipline (Z) has a significant positive effect on employee performance (Y). The results of Path Analysis on hypotheses 6 and 7, namely work discipline (Z) cannot mediate the relationship of job training (X1) to employee performance (Y), Work Discipline (Z) cannot mediate the relationship between motivation (X2) and employee performance (Y) .